The Effect Of Cyclohexanone Exposure On Incidence Of Irritant Contact Dermatitis - Denta Aditya Episana; Dewi Sumaryani Soemarko; Indah Suci Widyahening (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: Skin disorders or abnormalities occur in more than 35% of all occupational disorders. Contact dermatitis is the most recognized occupational disease in many countries (with irritant contact dermatitis accounting for 80% of the cases), yet these cases are often not reported. One of the causes of irritant contact dermatitis is Cyclohexanone, a chemical recognized as an oxidizing agent that can irritate the skin. This evidence-based case report aims to gather evidence about the effect of cyclohexanone exposure on the incidence of irritant contact dermatitis.Method: The case in this study is about a 37-year-old woman who worked as a logo printing operator in a shoe manufacturing company that is exposed to cyclohexanone and was diagnosed with irritant contact dermatitis. A literature search was conducted through PubMed, Scopus, and ProQuest and performed with the hand searching method. The inclusion criteria included systematic review study, cohort study, case-control study, cross-sectional study, irritant contact dermatitis, cyclohexanone, and occupational. Then, critically appraised using relevant criteria by the Oxford Center for Evidence-Based Medicine. Result: Three relevant cross-sectional studies were found through literature searching and are critically appraised. The estimate’s magnitude and precision regarding the association between the exposure and outcome in the first study cannot be assessed; the study only stated no statistically significant p-value in the prevalence of occupational skin dermatitis between departments and the examination between departments. The second study showed that workers with solvent chemical mixture exposure, including cyclohexane, are correlated with skin symptoms, dry or itchy skin on the hands or arms, POR 1.46 (95% CI 1.06-2.01), and redness on hands or arms, POR 1.50 (95% CI 1.09-2.70). In comparison, the third study showed that workers with a high dermal single exposure to cyclohexane have a higher risk for the incidence of hand dermatitis OR 2.15 (95% CI 0.59-7.95) without any statistical significance.Conclusion: The available evidence from cross-sectional studies did not prove an association between cyclohexanone exposure and irritant contact dermatitis in workers; only one study shows a significant association statistically. However, it is recommended to provide tools to prevent direct contact with the chemical; workers should also wear appropriate protective gloves to avoid occupational irritant contact dermatitis. A better study design such as cohort or case-control is needed to provide substantial evidence that cyclohexanone exposure can cause irritant contact dermatitis in workers.